A SIMULATION OF AUTOMATIC ELECTRIC ENERGY SCHEDULING SYSTEM IN HOUSEHOLD INSTALLATIONS BASED ON MICROCONTROLLER - Irwan Roganda Malau; Zuraidah Tharo; Solly Aryza; Muhammad Rizki Syahputra; Eddy Sutejo (Jurnal Scientia, 2023)
Efforts to save electrical energy needed by the community by utilizing microcontrollers. The microcontroller contains a program in the form of instructions that will be used to execute the microcontroller system. In this design, a microcontroller connected to the circuit will turn on the relay. This series of electrical energy scheduling systems is formed with several main components, namely an integrated circuit of Microcontroller, Relay, RTC, Bluetooth Module, MCB (Miniature Circuit Breaker).The system created can also be controlled manually via smartphone. Control via smartphone is local because it uses a Bluetooth connection. The control basis for the automatic electrical energy system is an AVR microcontroller, namely Atmega 16. The working principle is based on reading the time or clock (RTC). When the microcontroller starts working, the microcontroller will read the clock on the RTC module, namely DS1307.